תשובה:
#y '= 1 + 12 (x + sin ^ 2 (x)) ^ 11 (1-2sin (x) cos (x)) #
הסבר:
בעיה זו נפתרת באמצעות כלל השרשרת:
# d / dx f (g (x)) = f '(g (x)) g' (x) #
# x = + + (x + sin ^ 2 (x)) ^ 3) ^ 4 = x + (x + sin = 2 (x)) ^ 12 #
נטילת הנגזרת:
# (dy) / dx = d / dx x + d / dx (x + sin = 2 (x)) ^ 12 #
# 1 + 12 (x + חטא ^ 2 (x)) ^ 11 * (d / dx (x + sin = 2 (x))) #
# (1 + 1 + 12) x + חטא ^ (x)) ^ 11 * (d / dx x + d / dx sin ^ 2 (x)) #
# 1 + 12 (x + sin = 2 (x)) ^ 11 * (1 + 2sin (x) (d / dx sin (x)) #
# # 1 + 12 (x + sin ^ 2 (x)) ^ 11 (1 - 2sin (x) cos (x) #